Study the relationship between serum lipid profile and bronchial asthma exacerbation - Israa S.M.M. Elkordi; Manal R. Hafez; Hoda A. Eid (Al-Azhar Assiut Medical Journal)
Background and aim Asthma is triggered by allergic and oxidative stress that starts lipid peroxidation with stimulation to release of arachidonic acid from cell membrane. This work aimed to study lipid profiles in bronchial asthma and to assess its use as a biomarker for its exacerbation. Patients and methods A total of 50 individuals with bronchial asthma participated in this case-control research. During both acute and stable asthma episodes, spirometric indices, arterial blood gasses, serum cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-c), and high-density lipoprotein cholesterol (HDL-c) levels were examined. Results In the acute phase, HDL was lower and LDL-c was greater in serum than in the stable period. TG, TC, and LDL-c were negatively linked in the acute phase, whereas HDL-c was favorably correlated with all spirometric indices. TG, TC, and LDL were negatively correlated with PaO2 and positively correlated with HCO3. HDL-c positively correlated with O2 saturation and PaO2, and negatively correlated with PaCO2 and HCO3. The most significant risk factors for dyslipidemia in acute phase were O2 saturation, PaO2, FVC%, HCO3, Forced Expiratory Flow (FEF) 25–75%, PaCO2, forced expiratory volume /forced vital capacity ratio. Serum HDL-c could be used to discriminate between acute and stable phases with 64% sensitivity, 68% specificity, 66.7% positive predictive value and 56.4% negative predictive value. Serum LDL could be used to discriminate between acute and stable phases with 70% sensitivity, 64% specificity, 66% positive predictive value and 68.1% negative predictive value. Conclusion Lipid profile was altered in asthma exacerbation. HDL-c and LDL-c could be used to discriminate between acute and stable asthma phases.